Current situation of groundwater in Costa Rica and future challenges on its management - Vargas-Azofeifa, Ingrid (2024)
Groundwater is key in the development of different socioeconomic activities in the country, it is also the largest concessioned source for public supply, tourist-commercial and industrial uses and although in the other uses such as irrigation, agroindustrial and agriculture predominate surface sources, these also use groundwater. Since 2000, there have been significant advances in research into some of the country’s aquifers; currently the area covered is 20 %, however, groundwater has not had the relevance it deserves, that is why pollution problems from anthropogenic sources have already occurred due to the lack of land planning and the weak application of protection and control measures; on the other hand, geogenic contamination is also present and it is associated with the natural geotectonic setting of the country. Groundwater governance in Costa Rica must be strengthened through the application of current regulations. Although efforts have been made for inter-institutional coordination, more resources must still be allocated to strengthen the country’s research. The greatest challenges occur in water governance, the control of illegal drilling and the implementation of tools to protect groundwater quality.